Production of High-Titer Epstein-Barr Virus Recombinants Derived from Akata Cells by Using a Bacterial Artificial Chromosome System - Kanda, Teru (American Society for Microbiology, 2004)
An Epstein-Barr virus (EBV) genome in Burkitt's lymphoma-derived cell line Akata was cloned into a bacterial artificial chromosome (BAC) vector. The BAC clone, designated AK-BAC, was rapidly and precisely modified by means of efficient homologous recombination in Escherichia coli. This system was used to produce recombinant EBVs with transgenes. An expression cassette of green fluorescent protein (GFP) was inserted into AK-BAC, and the resultant BAC clone, AK-BAC-GFP, was transfected into Akata cells. We found that transfected BAC plasmids efficiently formed episomes in EBV-positive Akata cells. Mixtures of wild-type and AK-BAC-GFP viruses were then produced and used to infect EBV-negative Akata cells. We obtained cell clones that harbored only AK-BAC-GFP but no wild-type episome. These cell clones produced infectious viruses after stimulating virus production, and the recombinant viruses of AK-BAC-GFP efficiently immortalized primary B lymphocytes. We further revised the method so that any kind of cDNA could be rapidly inserted into the unique I-PpoI site that had been artificially introduced into AK-BAC. The AK-BAC system will have a broad range of applications, such as genetic analyses of various viral gene products and development of viral vectors for human gene therapy.